The Development of Project Based Learning Models Assisted by Digital Modules in the Digital Simulation Subjects of SMK Texmaco Semarang - Munandar, Aris; Wibawanto, Hari; Kustiono, Kustiono (Innovative Journal of Curriculum and Educational Technology, 2018)
Education has been developing rapidly with the advances in digital technology. Creative demands in the innovation of the learning process of the current situation must have by educators and learners. This study has purpose to determine the procedure of learning development of digital simulation assisted by digital module by using digital module based Portable Document Format, produced digital module, and determine the effectiveness of learning by using digital modules based Portable Document Format to grade X of RPL and TKJ Skill Competency on the subjects of Digital Simulation at SMK Texmaco Semarang. This study applied the Research and development (R & D) method by using a five-stage process of the development of digital module based Portable Document format on the subject of digital Simulation. The subjects of this study were students of grade X of RPL and TKJ Skills Competency on the subject of Digital Simulation, SMK Texmaco Semarang. The results showed that the average value of students who use digital module based Portable Document Format (New Work System), ie 91.7%, in the conventional learning (Old Job System), with 74%. The procedure of the development of digital module based Portable Document Format consists of five stages, which is in accordance to the research and development proposed by Borg and Gall, pre-development model, development model, evaluation model, implementation and revision model. Based on the results of this study, it can be concluded that learning by using digital module based Portable Document Format is effective as can be seen from the response of students with an average score of 57.13% (excellent). The benefits obtained from the study are (1) provide benefits of the repertoire of knowledge in the utilization of information and communication technologies, particularly in the project-based learning model assisted by digital module, (2) as a reference for subsequent researchers, mainly related to the digital module.